FLEXIBILITY OF INDUSTRIAL “PRODUCT-SERVICE” SYSTEM: IMPLEMENTATION AND MEANS OF MEASUREMENT - S. Panteleev (Модернизация, инновация, развитие, 2016)
Article is devoted to the analysis of the flexibility of industrial “product-service” systems (hereafter IPSS), meaning provision of adaptability to the changing needs of users along the life-cycle of IPSS. Flexibility of the system gives company-producer of the industrial equipment competitive advantages on the b-to-b market. Due to this reason development and improvement of the means of valuation of flexibility is an important field of study. Aim of the article is IPSS flexibility analysis and development of efficient means of flexibility valuation.Article tasks. Research the advantages of the IPSS flexibility; analyze problems that arise as the result of flexibility implementation; propose ways to solve these problems.Methodology. Methodological base of the article are the following scientific methods: deduction, comparative and individual analysis, methods of systematization and generalization of theoretical materials.Results. Conclusions / importance. Article proposes to use IPSS concept model that takes into consideration IPSS resources, actions and functions. With the help of this model switching options, that reflect the flexibility of IPSS, can be defi ned. Economic and technological aspects of changes should be taken into consideration with the help of integrated, iterative approach, that compares supplier costs on flexibility implementation and the clients desire to pay for it. At the same time supplier can calculate the potential profi t from provision of fl exibility. Thus, the basis for efficient decision making when the IPSS is structures is made.